Motivational factors that influencing knowledge sharing behaviour among academicians in IPG Batu Lintang, Kuching / Jusphine Owen Ulan and Zuraima Elza Ismail - Ulan, Jusphine Owen; Ismail, Zuraima Elza (2017)
This day, knowledge sharing is a process of interchanges the knowledge among individuals and also the groups. Promoting a knowledge sharing behaviour is a challenge for most organizations, including the educational institutions. Developing a behaviour which values and practices knowledge sharing is an effort involving attention to organizational and academicians perspective and performance. Therefore, this study expected to examine the knowledge sharing behaviour among academicians in IPG Batu Lintang and to cover areas such as organizational incentives towards knowledge sharing behaviour, enjoyment in helping others towards knowledge sharing behaviour, subjective norm towards knowledge sharing behaviour, perceived behavioural control towards knowledge sharing behaviour and the most dominant gender towards knowledge sharing behaviour. A questionnaire was used for collecting data and 73 academicians from IPG Batu Lintang participated in this study. Generally, organizational incentive and enjoyment in helping others have a positive influence towards knowledge sharing behaviour. Other than that, subjective norm also can be one of the factors that can influence the academicians towards knowledge sharing behaviour. Apart from that, the academicians also have a positive perceived behavioural control towards the knowledge sharing behaviour. The study revealed the dominant gender towards knowledge sharing behaviour. This study proposes further examine knowledge sharing behaviour by applying Theory of Planned Behaviour (TPB). Besides, this study also among the first research studies to investigate knowledge sharing behaviour among academicians in IPG Batu Lintang.